Negative plate and secondary battery thereof

By layering the coating of silicon carbon particles of different particle sizes in the active material layer of the negative electrode sheet, the problem of dust generated by silicon carbon negative electrode after laser drilling is solved, and the safety performance and cycle stability of the battery are improved.

CN119812199AInactive Publication Date: 2025-04-11ZHEJIANG LIWINON ELECTRONIC TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510018935.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The theoretical specific capacity of traditional graphite negative electrodes is close to the limit, which is difficult to meet the development needs of high-energy-density batteries. Moreover, the silicon carbon negative electrode generates a large amount of dust after laser drilling, affecting structural stability and safety performance.

Method used

Silicon carbon particles of different particle sizes are coated in the active material layer of the negative electrode sheet in a layer. By controlling the mass content and spherical degree of the first and second silicon carbon particles, the dust generation after laser drilling is reduced.

Benefits of technology

It effectively reduces the amount of dust after laser holes on the pole sheet, reduces the risk of puncture of silicon particles on the separator, improves the K value of the battery, and improves the safety performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005230732900000081
    Figure BDA0005230732900000081
  • Figure BDA0005230732900000091
    Figure BDA0005230732900000091
Patent Text Reader

Abstract

The invention discloses a negative plate and a secondary battery thereof. The negative plate comprises a current collector and an active material layer arranged on at least one surface of the current collector, the active material layer comprises a first active material layer and a second active material layer, the first active material layer comprises first silicon carbon particles, and the second active material layer comprises second silicon carbon particles; the average particle size of the first silicon carbon particles is d1, the average particle size of the second silicon carbon particles is d2, and d1 and d2 meet the relation that d2 / d1 is larger than 0.3 and smaller than 1. The sphericity degree of the first silicon particles is p1, the sphericity degree of the second silicon particles is p2, and p2 / p1 is more than or equal to 0.33 and less than or equal to 0.67. The active material layer adopts the silicon carbon particles with different particle sizes, and the content proportion of the two silicon carbon particles is controlled, so that the dust quantity and the dust particle size after laser drilling of the pole piece can be reduced, the risk of puncturing a diaphragm is reduced, the K value of the battery is reduced, and the safety performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a negative electrode sheet and a secondary battery thereof. Background Art

[0002] With the development of the industry, the market demand for the energy density of lithium-ion batteries continues to increase. The theoretical specific capacity of traditional graphite negative electrodes has reached its limit and it is difficult to meet the development needs of high energy density batteries. In contrast, silicon-carbon materials have a higher theoretical specific capacity. Combining them with graphite to form silicon-carbon negative electrodes has become an important technical route to improve battery energy density.

[0003] However, as the proportion of silicon-carbon content increases, silicon-carbon negative electrodes face problems such as poor fast charging performance and cycle stability in practical applications. In order to optimize the fast charging performance and cycle performance of the silicon-doped system, laser drilling technology was introduced, but it also brought new technical difficulties in actual production: First, after laser drilling, the silicon-carbon negative electrode is prone to produce a large amount of silicon particle dust, which not only affects the production environment, but also reduces the structural stability of the electrode; second, the detached silicon particles have high hardness and sharp edges, which can easily pierce the diaphragm during battery assembly and use, causing safety hazards; third, the detachment of silicon particles will lead to the loss of active substances, thereby affecting the self-discharge rate (K value) of the battery and reducing the overall performance of the battery.

[0004] Therefore, how to effectively control the dust generation during the laser drilling process, reduce the risk of silicon particles piercing the diaphragm, and reduce the K value of the battery while ensuring the safety performance and cycle stability of the fast-charging battery is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to provide a negative electrode sheet that can effectively control dust generation during laser drilling, reduce the risk of silicon particle dust piercing the diaphragm, and simultaneously reduce the K value of the battery.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A negative electrode sheet comprises a current collector and an active material layer disposed on at least one surface of the current collector;

[0008] The active material layer includes a first active material layer and a second active material layer, the first active material layer is disposed on the surface of the current collector, and the second active material layer is disposed on the outer surface of the first active material layer;

[0009] The first active material layer includes first silicon-carbon particles, and the second active material layer includes second silicon-carbon particles;

[0010] The average particle size of the first silicon-carbon particles is d1, and the average particle size of the second silicon-carbon particles is d2, wherein d1 and d2 satisfy the relationship: 0.3≤d2 / d1≤1;

[0011] The mass content of the first silicon-carbon particles is w1, and the mass content of the second silicon-carbon particles is w2, wherein w1 and w2 satisfy the relationship: 10%≤w2 / (w1+w2)≤60%, 0.11≤w2 / w1≤1.5;

[0012] The sphericity of the first silicon-carbon particles is p1, and the sphericity of the second silicon-carbon particles is p2, wherein p1 and p2 satisfy the relationship: 0.25≤p2 / p1≤0.67, 3≤p1≤4, 1≤p2≤2;

[0013] The particle size of the silicon-carbon particles, the silicon-carbon mass content and the silicon-carbon sphericity satisfy the following relationship: m*p2 / p1*d2 / d1=w2 / w1, 1.5≤m≤2, wherein m is a correction coefficient.

[0014] Preferably, the average particle size d2 of the second silicon-carbon particles satisfies: 5 μm<d2≤10 μm.

[0015] Preferably, said w1 and said w2 satisfy the relationship: 35%≤w2 / (w1+w2)≤44%, 0.54≤w2 / w1≤0.79.

[0016] Preferably, the first silicon-carbon particles are block particles, and the second silicon-carbon particles are spherical particles.

[0017] Preferably, the ratio of the coating surface density of the first active material layer to the coating surface density of the second active material layer is (4-6):(4-6).

[0018] Preferably, the ratio of the coating surface density of the first active material layer to the coating surface density of the second active material layer is 5:5.

[0019] Preferably, the thickness of the first active material layer is 40% to 60% of the total thickness of the negative electrode sheet, and the thickness of the second active material layer is 40% to 60% of the total thickness of the negative electrode sheet.

[0020] Preferably, the active material layer is provided with one or more concave holes by laser drilling process; the depth of the concave holes accounts for 55-65% of the total thickness of the active material layer.

[0021] The present invention also provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator spaced between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is any one of the negative electrode sheets described above.

[0022] Preferably, the K value of the secondary battery is 0.02-0.2.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects: the negative electrode of the present invention adopts silicon-carbon particles of different particle sizes in the first active material layer and the second active material layer respectively, and controls the content ratio of the two silicon-carbon particles, thereby effectively reducing the amount of dust after laser drilling of the electrode piece, reducing the probability of piercing the diaphragm, and helping to reduce the K value of the battery and improving the safety performance of the battery. DETAILED DESCRIPTION

[0024] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] According to a first aspect of the present invention, the present invention provides a negative electrode sheet, comprising a current collector and an active material layer arranged on at least one surface of the current collector; the active material layer comprises a first active material layer and a second active material layer, the first active material layer is arranged on the surface of the current collector, and the second active material layer is arranged on the outer surface of the first active material layer; the first active material layer comprises first silicon-carbon particles, and the second active material layer comprises second silicon-carbon particles; the average particle size of the first silicon-carbon particles is d1, and the average particle size of the second silicon-carbon particles is d2, wherein d1 and d2 satisfy the relationship: 0.3≤d2 / d1≤11<d1 / d2<3; the first The mass content of the silicon-carbon particles is w1, and the mass content of the second silicon-carbon particles is w2, wherein w1 and w2 satisfy the relationship: 10%≤w2 / (w1+w2)≤60%, 0.11≤w2 / w1≤1.5; the sphericity of the first silicon-carbon particles is p1, and the sphericity of the second silicon-carbon particles is p2, wherein p1 and p2 satisfy the relationship: 0.25≤p2 / p1≤0.67, 3≤p1≤4, 1≤p2≤2; the particle size of the silicon-carbon particles, the silicon-carbon mass content and the silicon-carbon sphericity satisfy the following relationship: m*p2 / p1*d2 / d1=w2 / w1, 1.5≤m≤2, wherein m is the correction coefficient.

[0026] The present invention coats silicon-carbon particles of different particle sizes on the current collector in layers and controls the mass content of the silicon-carbon particles in each layer; through the above relationship of the present invention, the self-discharge rate (i.e., K value) of the battery cell can be reduced, thereby improving the performance of the battery, extending the battery life, and improving the yield rate of the battery cell.

[0027] In some embodiments, the average particle size d2 of the second silicon-carbon particles satisfies: 5≤um<d2≤10um. The second silicon-carbon particles within the above range have a suitable particle size distribution, which effectively ensures the safety performance and rate performance of the battery. If the particle size of the silicon-carbon particles is too small, the larger the specific surface area, the more side reactions will occur, the internal resistance of the battery will increase, and excessive energy will accumulate, resulting in a temperature increase, thereby increasing safety hazards; at the same time, the increase in specific surface area also means that the contact area with the electrolyte increases, which may aggravate the formation and consumption of the SEI film and affect the cycle performance and safety of the battery; if the particle size of the silicon-carbon particles is too large, the specific surface area is smaller, and the contact area with the electrolyte is reduced, thereby affecting the embedding and extraction efficiency of lithium ions and reducing the energy density of the battery. At the same time, during the initial charge and discharge, the battery capacity is reduced and the irreversible capacity is reduced.

[0028] In some embodiments, w1 and w2 satisfy the relationship: 35% ≤ w2 / (w1+w2) ≤ 44%. The silicon-carbon content ratio within the above range, the K value range is 0.02 to 0.2. The battery cell K value and high temperature cycle retention rate are optimal; if it is lower than 35%, the improvement of the K value is not obvious; if it is higher than 44%, the high temperature cycle retention rate of the battery will be significantly deteriorated.

[0029] In some embodiments, the first silicon-carbon particles are block particles, and the second silicon-carbon particles are spherical particles. That is, spherical silicon-carbon is used in the second active material layer, and block particles are used in the first active material layer. Compared with block silicon-carbon particles, spherical silicon-carbon particles are more pressure-resistant, and the silicon-carbon breakage rate is low. The degree of silicon-carbon breakage is strongly related to the specific surface area of ​​the pole piece after rolling. After laser drilling, the amount and particle size of silicon-carbon dust will be reduced; however, in the existing system, the spherical silicon-carbon particles have less elastic connection with the binder due to their spherical structure. During the cycle, the silicon-carbon particles have a high expansion rate and the binder breaks, the pole piece is prone to cracks, the conductive network deteriorates, and the cycle retention rate deteriorates. Therefore, the mixing ratio of spherical silicon-carbon particles cannot be too high.

[0030] In some embodiments, the ratio of the coating surface density of the first active material layer to the coating surface density of the second active material layer is (4-6): (4-6). The coating surface density of the first active material layer is similar to the coating surface density of the second active material layer, and the process control during the coating process plays a decisive role in the consistency and stability of the surface density. The extreme difference in surface density can be controlled within a small range, thereby ensuring the consistency of battery performance.

[0031] In some embodiments, the ratio of the coating surface density of the first active material layer to the coating surface density of the second active material layer is 5:5. In the above, the first particles and the second particles coated in layers have different particle sizes. Under the same volume filling ratio, the larger the particle size of the material, the wider the particle size distribution, and the smaller the viscosity of the slurry, which is conducive to increasing the solid content and reducing the difficulty of coating. In addition, when the particle size distribution of the material is wide, the small particles in the system can be filled in the gaps of the large particles, which helps to increase the compaction density of the pole piece. Therefore, the combination of large and small particles of the first particles and the second particles can improve the volume energy density of the battery.

[0032] In some embodiments, the thickness of the first active material layer is 40% to 60% of the total thickness of the negative electrode sheet, and the thickness of the second active material layer is 40% to 60% of the total thickness of the negative electrode sheet.

[0033] In some embodiments, the active material layer is provided with one or more concave holes by laser drilling process; the depth of the concave holes accounts for 55-65% of the total thickness of the active material layer. Laser drilling technology can form micropores on the battery pole piece, which are conducive to the transmission of lithium ions and reduce the diffusion distance of lithium ions, thereby improving the cycle performance and rate performance of the battery.

[0034] A second aspect of the present invention is to provide a secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet described above.

[0035] In some embodiments, the K value of the secondary battery is 0.02-0.2. The smaller the K value, the lower the self-discharge rate of the battery and the better the battery performance.

[0036] The positive electrode sheet of the present invention comprises a positive electrode current collector and a positive electrode active material layer coated on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer is LiCoO 2 、LiNiO 2 、LiMnO 2 、LiMn 2 O 4 、LiMnPO 4 、LiFePO 4 、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 、LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.8Co 0.1 Mn 0.1 O 2 、LiNi 0.85 Co 0.15 Al 0.05 O 2 One or more of the positive electrode collector; the positive electrode collector can be various materials in the art suitable for use as a positive electrode collector for lithium-ion batteries. For example, the positive electrode collector can be, but is not limited to, metal foil, and more specifically, can be, but is not limited to, aluminum foil, and the like.

[0037] The separator in the present invention can be any material suitable for lithium-ion battery separators in the art, for example, it can be a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers, etc., but not limited to.

[0038] The secondary battery of the present invention further comprises an electrolyte, which comprises an organic solvent, an electrolyte lithium salt and an additive. The electrolyte lithium salt may be LiPF used in a high temperature electrolyte. 6 and / or LiBOB; it can also be LiBF used in low temperature electrolytes 4 、LiBOB、LiPF 6 It can also be LiBF used in the overcharge-proof electrolyte 4 、LiBOB、LiPF 6 , LiTFSI; it can also be LiClO 4 、LiAsF 6 、LiCF 3 SO 3 、LiN(CF 3 SO 2 ) 2 At least one of the above. The organic solvent may be a cyclic carbonate, including PC, EC; it may also be a chain carbonate, including DFC, DMC, or EMC; it may also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to film-forming additives, conductive additives, flame retardant additives, overcharge prevention additives, and additives for controlling H in the electrolyte. 2 At least one of an additive for increasing the content of O and HF, an additive for improving low temperature performance, and a multifunctional additive.

[0039] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.

[0040] Example 1

[0041] Preparation of positive electrode: Active material LiCoO 2 Conductive agent acetylene black, conductive carbon nanotubes, and binder polyvinylidene fluoride (PVDF) are fully dispersed in an N-methylpyrrolidone solvent system in a weight ratio of 97.8:0.6:0.4:1.2 and evenly coated on the aluminum current collector, and then cold-pressed and sliced ​​to obtain the positive electrode sheet.

[0042] Preparation of negative electrode sheet: The second active material (spherical silicon carbon + graphite with a particle size range of 5 to 9 μm), SuperP, sodium carboxymethyl cellulose, and styrene butadiene rubber (SBR) emulsion are mixed in a weight ratio of 96.5:0.5:1.2:1.8 to obtain a second active material layer slurry; the first active material (blocky silicon carbon with a particle size range of 10 to 15 μm and graphite 1), SuperP, sodium carboxymethyl cellulose, and styrene butadiene rubber (SBR) emulsion are mixed in a weight ratio of 96.5:0.5:1.2:1.8 to obtain a first negative electrode active material layer slurry, the first active material slurry is coated on the copper current collector to obtain the bottom first active material layer, and then the second active material slurry is coated on the first active material layer to obtain a second active material layer (the upper and lower layers are coated with a surface density of 5:5), and then cold pressed and slit to obtain a negative electrode sheet.

[0043] The negative electrode sheet after stripping is laser punched, and the punching depth is 60% of the thickness of the active material layer of the electrode sheet.

[0044] Diaphragm: The PE surface is coated with a ceramic mixture as a separator.

[0045] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) were mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF 6 It is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0046] Preparation of lithium-ion batteries: The positive electrode sheets, separators, and negative electrode sheets are wound or stacked to produce bare cells, which are then packaged and injected with electrolyte to produce finished lithium-ion batteries.

[0047] Example 2

[0048] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0049] The rest is the same as in Example 1 and will not be described again here.

[0050] Example 3

[0051] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0052] The rest is the same as in Example 1 and will not be described again here.

[0053] Example 4

[0054] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0055] The rest is the same as in Example 1 and will not be described again here.

[0056] Example 5

[0057] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0058] The rest is the same as in Example 1 and will not be described again here.

[0059] Example 6

[0060] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0061] The rest is the same as in Example 1 and will not be described again here.

[0062] Example 7

[0063] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0064] The rest is the same as in Example 1 and will not be described again here.

[0065] Example 8

[0066] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0067] The rest is the same as in Example 1 and will not be described again here.

[0068] Comparative Example 1

[0069] The difference from Example 1 is that the second silicon-carbon particles are not added.

[0070] The rest is the same as in Example 1 and will not be described again here.

[0071] Comparative Example 2

[0072] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0073] The rest is the same as in Example 1 and will not be described again here.

[0074] Comparative Example 3

[0075] The difference from Example 1 is the content of the second silicon-carbon particles, as shown in Table 1;

[0076] The rest is the same as in Example 1 and will not be described again here.

[0077] The above Examples 1 to 8 and Comparative Examples 1 to 3 are sorted out as shown in Table 1.

[0078] Table 1

[0079]

[0080] The lithium-ion batteries obtained in the above-mentioned Examples 1 to 8 and Comparative Examples 1 to 3 were subjected to the following performance tests. 1) K value = (V2-V1) / T; V1 is the test voltage after two days of high temperature storage, V2 is the test voltage after two days of normal temperature storage, and T is the interval between V1 and V2;

[0081] 2) Liquid nitrogen resistance: Soak the battery cell in liquid nitrogen (1-2 minutes), connect the battery cell tabs with a multimeter, and test the liquid nitrogen resistance of the battery cell (resistance requirement ≥ 0.4MΩ)

[0082] 3) 45-degree cycle attenuation rate refers to the percentage of the remaining capacity of the battery cell when it is charged to 4.2V at 3C level and charged to the cut-off voltage at a conversion rate of 1.8C and cycled 500 times to the initial capacity, which is required to be >80%.

[0083] 4) Specific surface area: the unit of area of ​​a material per unit mass (m 2 / g)

[0084] The test results are shown in Table 2 below.

[0085] Table 2

[0086]

[0087] It can be seen from the test results of the embodiment and the comparative example that when the silicon content in the second particle increases, the number of silicon dust particles decreases and the particle size decreases. The liquid nitrogen resistance increases and the K value decreases. When the silicon carbon content of the second active material layer is 0%, the laser drilling only hits the block silicon carbon (high crushing rate and large particle size after rolling), the number and particle size of silicon dust particles are large, and the K value is the largest. However, it has a good connection with the binder and the conductive network, and the capacity attenuation rate is the highest.

[0088] When the silicon content in the second particle is 10% to 60%, the laser drilling simultaneously hits the upper and lower layers of silicon carbon with two morphologies, and the spherical silicon carbon content continues to increase, the number of silicon dust particles and the particle size value continue to decrease, and the K value continues to decrease. However, due to the continuous increase in the spherical silicon carbon, its elastic connection with the binder is less, the pole piece has cracks, the conductive network is greatly damaged, and the capacity attenuation rate continues to deteriorate; therefore, when the silicon content in the second particle is 40% to 44%, the comprehensive performance is optimal.

[0089] In summary, the present invention provides a negative electrode sheet and a secondary battery thereof, wherein the negative electrode sheet is coated with silicon-carbon particles of different particle sizes in layers and the content ratio of the two silicon-carbon particles is limited, which can reduce the amount of dust after laser drilling of the electrode sheet, reduce the probability of piercing the diaphragm, improve the K value, and improve the safety performance of the battery.

[0090] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A negative electrode sheet, characterized in that: It includes a current collector and an active material layer disposed on at least one surface of the current collector; The active material layer includes a first active material layer and a second active material layer, the first active material layer is disposed on the surface of the current collector, and the second active material layer is disposed on the outer surface of the first active material layer; The first active material layer includes first silicon-carbon particles, and the second active material layer includes second silicon-carbon particles; The average particle size of the first silicon-carbon particles is d1, and the average particle size of the second silicon-carbon particles is d2, wherein d1 and d2 satisfy the relationship: 0.3≤d2 / d1≤1; The mass content of the first silicon-carbon particles is w1, and the mass content of the second silicon-carbon particles is w2, wherein w1 and w2 satisfy the relationship: 10%≤w2 / (w1+w2)≤60%, 0.11≤w2 / w1≤1.5; The sphericity of the first silicon-carbon particles is p1, and the sphericity of the second silicon-carbon particles is p2, wherein p1 and p2 satisfy the relationship: 0.25≤p2 / p1≤0.67, 3≤p1≤4, 1≤p2≤2; The particle size of the silicon-carbon particles, the silicon-carbon mass content and the silicon-carbon sphericity satisfy the following relationship: m*p2 / p1*d2 / d1=w2 / w1, 1.5≤m≤2, wherein m is a correction coefficient.

2. The negative electrode sheet according to claim 1, characterized in that: The average particle size d2 of the second silicon-carbon particles satisfies: 5 μm<d2≤10 μm.

3. The negative electrode sheet according to claim 1, characterized in that: The w1 and the w2 satisfy the relationship: 35%≤w2 / (w1+w2)≤44%, 0.54≤w2 / w1≤0.

79.

4. The negative electrode sheet according to claim 1, characterized in that: The first silicon-carbon particles are block particles, and the second silicon-carbon particles are spherical particles.

5. The negative electrode sheet according to claim 1, characterized in that: The ratio of the coating area density of the first active material layer to the coating area density of the second active material layer is (4 to 6):(4 to 6).

6. The negative electrode sheet according to claim 5, characterized in that: The ratio of the coating area density of the first active material layer to the coating area density of the second active material layer is 5:

5.

7. The negative electrode sheet according to claim 1, characterized in that: The thickness of the first active material layer is 40% to 60% of the total thickness of the negative electrode sheet, and the thickness of the second active material layer is 40% to 60% of the total thickness of the negative electrode sheet.

8. The negative electrode sheet according to claim 1, characterized in that: The active material layer is provided with one or more concave holes by laser drilling process; the depth of the concave holes accounts for 55-65% of the total thickness of the active material layer.

9. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, characterized in that: The negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 8.

10. The secondary battery according to claim 9, characterized in that: The K value of the secondary battery is 0.02 to 0.2.

Citation Information

Patent Citations

  • Silicon carbon composite microsphere, and preparation method and application thereof

    CN106384825A

  • Negative pole piece as well as preparation method and application thereof

    CN118712340A

  • Lithium ion secondary battery, assembly for preparing lithium ion secondary battery, preparation method and electric device

    CN119069644A

  • Battery

    CN119133445A

  • Nonaqueous electrolyte and nonaqueous electrolytic secondary battery

    JP2013218967A

Cited By

  • Negative electrode sheet and secondary battery comprising same

    WO2026144347A1